ADAPTIVE GROWTH TECHNIQUE OF TRUSS STRUCTURE BASED ON MMA - HUA Min; DING XiaoHong; WU ChunPing (Jixie qiangdu)
The existing adaptive growth technique deducted the optimization iteration formula according to the condition named Karush-Kuhn-Tucker condition. It is high efficiency and good, which is aimed to strain energy and bound to the volume against optimization problem of stiffener distribution for plate and shell structures. However, different optimization iteration formula, which deducted by different kinds of problem, is poor and difficult to generalize, especially for the optimization problems with more than one constraint. Against with the lack of adaptive growth technique, a new method that is moving asymptotes（MMA） is suggested by this article and the adaptive growth technique is applied to truss structure topology optimization design. The design of typical truss structures with single constraint and multiple constraints is discussed, and the multi load cases are studied. The results of numerical examples show that the proposed method can obtain clear information of rod distribution and dimension, and has high design efficiency and good applicability. It is convenient for practical machining and has a good application prospect.